PERSPEKTIF PRILAKU POLA HIDUP SEHAT DAN AKTIVITAS FISIK LANJUT USIA DILIHAT DARI KONTEKS SOSIOKULTURAL - Haeril, Haeril (Journal of Sport Science And Physical Education (JOSEPHA), 2025)
The growing number of elderly population in Indonesia demands attention to their quality of life, especially in terms of healthy lifestyle and physical activity. This study aims to explore the elderly's perspective on healthy lifestyle and physical activity behaviors from a socio-cultural context. Using a qualitative approach with a phenomenological study method, data were collected through in-depth interviews and observations of 12 elderly people from two different cultural communities (coastal village and mountain village). The results showed that the elderly's perception of health tends to be passive and influenced by cultural values and past life experiences. Physical activities carried out are more socially and spiritually meaningful, such as mutual cooperation and attending religious studies, compared to formal sports such as elderly gymnastics which are considered culturally foreign. In addition, the role of family and social environment has a significant influence on the behavior of the elderly in maintaining diet and health. These findings emphasize the importance of a health promotion approach that is sensitive to local cultural and social contexts, as well as the need to involve families and communities in elderly health interventions.